I CAN’T SEEM TO FIND MY GLASSES – THE ENGLISH VERB SEEM AND ITS MACEDONIAN TRANSLATION (Philological Studies, 2020)
This paper discusses the verb seem and its translation equivalents in Macedonian. Seem is a multifunctional verb. As a copula verb, it is a verb of indirect perception. It may also mark the verb phrase for evidentiality and epistemic modality. In other cases, seem may also function as a hedge, which is a pragmatic function of linguistic means that allows the speaker not to express the commitment categorically. Because of its multiple functions, seem has different translations in Macedonian. The most widespread are congruent correspondences, when seem is translated with a corresponding verb (се чини, изгледа, личи), and zero correspondences, when it is dropped. This variety may also appear due to different cultural attitudes towards evidence.
Keywords: translation; culture; evidentiality; epistemic modality